Clinicopathological Relevance of PAX8 Expression Patterns in Acute Kidney Injury and Chronic Kidney Diseases - Maja Zivotic; Dusko Dundjerovic; Radomir Naumovic; Sanjin Kovacevic; Milan Ivanov; Danijela Karanovic; Gorana Nikolic; Jasmina Markovic-Lipkovski; Sanja Radojevic Skodric; Jelena Nesovic Ostojic (Diagnostics, 2022)
Transcription factor PAX8, expressed during embryonic kidney development, has been previously detected in various kidney tumors. In order to investigate expression of PAX8 transcription factor in acute kidney injury (AKI) and chronic kidney diseases (CKD), immunohistochemical analysis was performed. Presence, location and extent of PAX8 expression were analyzed among 31 human kidney samples of AKI (25 autopsy cases, 5 kidney biopsies with unknown etiology and 1 AKI with confirmed myoglobin cast nephropathy), as well as in animals with induced postischemic AKI. Additionally, expression pattern was analyzed in 20 kidney biopsy samples of CKD. Our study demonstrates that various kidney diseases with chronic disease course that results in the formation of tubular atrophy and interstitial fibrosis, lead to PAX8 expression in the nuclei of proximal tubules. Furthermore, patients with PAX8 detected within the damaged proximal tubuli would be carefully monitored, since deterioration in kidney function was observed during follow-up. We also showed that myoglobin provoked acute kidney injury followed with large extent of renal damage, was associated with strong nuclear expression of PAX8 in proximal tubular cells. These results were supported and followed by data obtained in experimental model of induced postischemic acute kidney injury. Considering these findings, we can assume that PAX8 protein might be involved in regeneration process and recovery after acute kidney injury. Thus, accordingly, all investigation concerning PAX8 immunolabeling should be performed on biopsy samples of the living individuals.